(untitled) (Scientific journal of the Fergana State University, 2023)
In the article have been explored final targets of modern education, the issues of breading professional as a fully developed person. The ultimate goal of modern teaching in an educational institution is depends of social needs of the specialist focused on socio-economic requirements. There are considered basic approaches to the formation of students’ intellectual culture.